Analisis Risiko Jasa Rental Mobil Pada CV. Mawar Rental Car - Anggita Pangaribuan; Mona Romaito; Kevin Heston (Maeswara : Jurnal Riset Ilmu Manajemen dan Kewirausahaan, 2024)
The purpose of this research is to analyze and determine possible risks that occur in car rental services, making it easier for companies to take action to prevent risks that can occur at CV Mawar Rental Car. The risks that arise come from internal factors that cause this company to experience losses. This research uses a quantitative research approach. The research location is on Jalan Setia Budi No. 12, Medan, North Sumatra. The data collection techniques used in this research were kuesioner. from the results of research at CV. Mawar Rental Car, the first thing to do is identify risks originating from operational risk, financial risk, external risk.